Reference and Inference of Song Lyrics in the Album Monochrome Written by Tulus - Dewirsyah, Amnur Rifai (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study aims to determine the use of references and inferences contained in the lyrics of existing songs in the album Monokrom Tulus work. The data source in this research is 1 lyric of 10 song lyrics contained in the album Monokrom Tulus work. The type of this research is descriptive method obtained by observation technique followed by documentation study done by listening / reading, understanding, then collecting and analyzing data based on reference and inference approach. Based on the results of the research, it can be seen that the use of references in the lyrics of songs in the album Monochrome in general amounted to 11 data, 8 pertained personal references (3 personal reference data anaphora and 5 personal reference data katafora), 2 data including comparative reference which all include comparative reference katafora, and the last one is anaphoric demonstrative reference data. While the inference that the authors found there are words that are implied in the lyrics of the song in the album Monochrome which makes the results of the inference yaang authors find may be different from other readers. As for the results that the authors find, there are some inexhaustible conclusions or do not support the information / conclusions on the previous fragment, but in the final inference the authors link them or draw conclusions based on common logic and dominant inferences that are interrelated.